Composite positive electrode containing coated carbon fiber and all-solid-state battery including the same
By using oxide-covered carbon fibers in solid-state battery anode cells, the problem of excessively rapid decomposition of the anode electrolyte is solved, and higher cycle stability and energy density are achieved.
Patent Information
- Application Number
- JP2024547198
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-07-15
- Filing Date
- 2023-05-24
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-05-24
AI Technical Summary
In the prior art, the problem of decomposition of anode electrolytes in solid-state batteries has not been effectively solved, resulting in the decomposition of electrolytes in the anode layer too fast, affecting the cycle stability and energy density of the battery.
An anode cell structure is adopted where carbon fiber is coated with oxide materials (such as Li3B11O18), in which carbon fibers and anode active material particles form electrical contact through a compaction process, thereby reducing the decomposition reaction between the anode electrolyte and the carbon fiber interface.
By reducing the decomposition of the anode electrolyte, the cycle stability and initial capacity of the solid-state battery are improved, while maintaining high utilization rate of anode active substances, extending the service life of the battery.
Smart Images

Figure 2025511439000001_ABST
Abstract
Description
Description of Related Applications
[0001] This application claims the benefit of U.S. Provisional Patent Application No. 63 / 389,383, filed July 15, 2022, and U.S. Provisional Patent Application No. 63 / 350,665, filed June 9, 2022, the contents of each of which are incorporated herein by reference in their entirety. [Technical field]
[0002] The present disclosure relates to a positive electrode layer or a positive electrode composite layer for an all-solid-state battery. [Background technology]
[0003] All-solid-state batteries (ASSBs) are considered promising candidates for future energy storage devices because they allow the use of lithium metal as the anode material, which would result in higher specific energy compared to conventional lithium-ion batteries based on organic liquid electrolytes. Thiophosphate-based solid electrolytes (SEs) appear to be particularly promising due to their high ionic conductivity, good mechanical compatibility, and relatively low cost. In general, the poor thermodynamic stability, chemical-mechanical bonding, and interfacial kinetics of SEs are the remaining major challenges. In the cathode composite, side reactions include a) decomposition at the current collector / SE interface at high potentials, b) reactions between the cathode active material (CAM) and SE, which result in a resistive interfacial layer, and c) decomposition reactions at the carbon / SE interface when a carbon conductive additive is used. Excessive decomposition of SEs can lead to the formation of Li in the cathode layer. + This can reduce mobility and lead to capacity fading over time.
[0004] Composite positive electrodes containing carbon fibers (CF), such as vapor grown carbon fibers (VGCF), provide higher initial capacity compared to the corresponding ASSBs without CF, as more CAM particles are electrically connected, enhancing CAM utilization. However, the initial capacity is not maintained, and rapid capacity fade is observed during cycling of the cell due to the increasing rate of SE decomposition (both from the CAM / SE and / or CF / SE interfaces). When the potential is outside the potential stability range of the SE, e.g., LPS (Li7P3S 11) For electrolytes above 2.1 V, sulfide SEs decompose at the CAM / SE and / or CF / SE interfaces.
[0005] To minimize the impact of SE decomposition, it is extremely important to reduce SE decomposition in positive electrode composite layers, especially those with a high CAM content, e.g., 86 wt % or more, and a low SE content, e.g., 14 wt % or less.
[0006] Patent Document 1 describes vapor grown carbon fiber (VGCF) coated with an electrically insulating material such as boron nitride as a thermally conductive electrically insulating filler. However, the resistivity of the coated VGCF disclosed therein is less than 10×10 3 Ω·cm or more, which can block electrical connection paths as required for the electrode layers.
[0007] Patent document 2 discloses an all-solid-state battery using carbon fiber as a conductive agent in the CAM layer to improve initial capacity due to increased utilization of the CAM by increasing the electronic conduction pathways. Patent document 3 discloses an all-solid-state battery using a conductive carbon additive in the cathode layer. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] U.S. Patent No. 7,150,911 B2 [Patent Document 2] US Patent Application Publication No. 2015 / 0228966A1 [Patent Document 3] U.S. Patent No. 9,219,271 B2 Summary of the Invention [Problem to be solved by the invention]
[0009] However, none of them disclose coated carbon materials. SE decomposition remains a problem. [Means for solving the problem]
[0010] In one embodiment, the present disclosure provides a method for producing a CAM-based solid electrolyte comprising the steps of: 11 O 18 The present disclosure provides a cathode layer comprising carbon fiber (CF) coated with VGCF, where the CAM particles are in electrical contact with the CF, for example, upon application of pressure during fabrication. In one embodiment, the present disclosure provides an all-solid-state battery comprising the cathode layer. In one embodiment, the ASSB has increased capacity and cycling stability due to reduced SE decomposition at the VGCF / SE interface. [Brief description of the drawings]
[0011]
Figure 1
Figure 2
Figure 3
Figure 4
[0012] In one embodiment, the present disclosure provides a cathode composite layer comprising particles of cathode active material (CAM) (1), a sulfide-based solid electrolyte (2), and carbon fibers (3) coated with an oxide material (4). In one embodiment, a typical structure is shown in FIG.
[0013] In one embodiment, the sulfide solid electrolyte used in the present disclosure may be any sulfide solid electrolyte containing Li and S and having the desired lithium ion conductivity. The sulfide solid electrolyte may be any crystalline material, glass ceramic, or glass. Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiHa (where "Ha" is one or more halogen elements), Li2S-P2S5-P2O5, Li2S-Li3PO4-P2S5, Li3PS4, Li4P2S6, Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li7P3S 11 , Li 3.25 P 0.95 S4, and Li 7-x P.S. 6-x Ha x(The argyrodite-type solid electrolyte, where "Ha" is one or more halogen elements and 0.2 < x < 1.8) can be mentioned. The concentration in the positive electrode layer is between 1% by mass and 30% by mass.
[0014] In one embodiment, as the conductive carbon fiber, without limitation, vapor-grown carbon fiber (VGCF), carbon nanotube (CNT), multi-walled carbon nanotube (MWCNT), carbon nanofiber, and graphite fiber can be mentioned. CF has a BET measurement specific surface area between 1 and 600 m 2 / g, and an electrical resistance of 0.5 Ω·cm or less. In one embodiment, the fiber has a concentration between 0.01% by mass and 5% by mass in the positive electrode layer.
[0015] In one embodiment, the oxide material is an electrical insulating material. In one embodiment, the oxide material is an inorganic oxide material. In one embodiment, the oxide material contains Li, a second element, and a third element. In one embodiment, the second element is one or more elements from Groups 15 and 16 of the periodic table such as O, N, S, P, etc. In one embodiment, the third element is one or more elements from Groups 13 and 14 of the periodic table such as B, C, Al, Si, Ga, and Ge or a transition metal. In one embodiment, the oxide material is an oxide containing Li, B, and one or two or more elements selected from the group consisting of, for example, B, Nb, Ti, Zr, Ta, Zn, W, and Al. In one embodiment, the oxide material, without limitation, is lithium borate, alumina, lithium zirconate (Li2ZrO3), LiNbO3, Li4SiO4, Li3PO4, Li2SiO3, LiPO3, Li2SO4, Li2WO4, Li2MoO4, LiAlO2, Li2TiO3, Li4Ti5O 12 , or an inorganic oxide material including its composite oxide. In one embodiment, as lithium borate, without limitation, Li3B 11 O 18 , Li3BO3, Li4B2O5, Li6B4O9, LiBO2, Li2B4O7, Li3B7O 12In one embodiment, the inorganic oxide is any other material that has a wide potential window of stability, for example, from 1.9 V to 5.0 V. For example, the inorganic oxide material is Li / Li + In one embodiment, the inorganic oxide material has a stable potential window of at least 1.5 V with respect to Li / Li + In one embodiment, the inorganic oxide material has a stable potential window of at least 2.0 V with respect to Li / Li + In one embodiment, the inorganic oxide material has a stable potential window of at least 2.5 V with respect to Li / Li + In one embodiment, the inorganic oxide material has a stable potential window of at least 3.0 V with respect to Li / Li + In one embodiment, the inorganic oxide material has a stable potential window of at least 4.0 V with respect to Li / Li + In one embodiment, the inorganic oxide material has a stable potential window of at least 4.5 V with respect to Li / Li + It has a stable potential window of at least 5.1 V with respect to
[0016] In one embodiment, the positive electrode composite layer is sandwiched between the positive electrode current collector and the solid electrolyte layer. In one embodiment, the positive electrode composite layer is formed by coupling lithium ions (Li + ) and electrons (e - ) The positive electrode active material (CAM) requires both Li + The connectivity is mainly provided by small particles of sulfide-based SE in the cathode composite mixture, e - The connectivity is mainly provided by CF. This sulfide-based SE (such as LPS) has high Li + However, they generally have Li / Li at the CAM / SE, CF / SE, and current collector / SE interfaces. + It decomposes at potentials below 1.7 V or above 2.1 V vs. Li. The decomposition by-products are generally the lower Li +The decomposition of the positive electrode composite layer reduces the battery operating voltage window and hampers the ability to build high energy density batteries.
[0017] In one embodiment, the present disclosure discloses carbon fibers coated with an oxide material layer or coating for a positive electrode composite layer. In one embodiment, the coating is Li / Li + Li3B has a wide voltage stability window of 1.9 to 4.7 V 11 O 18 The present disclosure has discovered that the thickness of the oxide material layer is very important. A coating with a high thickness may completely block the electronic conduction pathway (which is essential to enable the operation of an all-solid-state battery). A coating with a low thickness may not make a difference compared to uncoated carbon fibers and may not reduce the decomposition. On the other hand, the coating has a certain thickness to provide a certain electrical insulation and thereby reduce the SE decomposition at the CF / SE interface. In one embodiment, the thickness is 1 nm or more. In one embodiment, the thickness is 2 nm or more. In one embodiment, the thickness is 5 nm or more. In one embodiment, the thickness is 10 nm or more. In one embodiment, the minimum thickness depends on several factors such as the composition of the coating, the intrinsic properties, and the interface between the coating and the CF. On the other hand, the coating is not too thick and is sufficient to withstand the battery formation (5000 lbs / in 2The coating has a thickness t that is thin enough to be penetrated by the hard CAM particles during the application of pressure (approximately 34.5 MPa) and thereby make electrical contact with the CAM particles and the VGCF. In one embodiment, the thickness is 200 nm or less. In one embodiment, the thickness is 150 nm or less. In one embodiment, the thickness is 100 nm or less. In one embodiment, the thickness is 80 nm or less. In one embodiment, the thickness is 50 nm or less. In one embodiment, the thickness is 30 nm or less. In one embodiment, the maximum thickness depends on several factors, such as the composition of the coating, the intrinsic properties, and the interface between the coating and the CF. In one embodiment, the cathode composite layer disclosed in the present disclosure significantly reduces the decomposition of SE and improves cycle life stability while achieving high initial specific capacity with near 100% CAM utilization. In one embodiment, the coating has a thickness of 1-5 nm. In one embodiment, the coating has a thickness of 1-20 nm. In one embodiment, the coating has a thickness of 1-50 nm. In one embodiment, the coating has a thickness of 1-80 nm. In one embodiment, the coating has a thickness of 1-100 nm. The present disclosure will be better understood with reference to the following experimental details, but those of skill in the art will readily recognize that the specific experiments detailed are for illustrative purposes only and are not intended to limit the present disclosure as described herein, as defined by the claims that follow.
[0018] In one embodiment, the oxide material is capable of transporting lithium ions in the positive electrode composite layer. Without intending to be bound by any theory, the lithium ion conductivity is attributed to defects in the crystal structure of the inorganic oxide and the relatively small activation energy required for the ion transport process. Islam, M. et al 2012 J. Phys.: Condens. Matter 24 203201.
[0019] In one embodiment, the present disclosure provides a composite layer as a positive electrode for an all-solid-state battery, the composite layer comprising particles of a positive electrode active material (CAM), a solid electrolyte, and carbon fibers coated with an oxide material, which in one embodiment is an electrically insulating material.
[0020] In one embodiment, the oxide material coated on the carbon fibers has a thickness of 1 to 80 nm.
[0021] In one embodiment, the oxide material coated on the carbon fibers has a thickness of 2 to 50 nm. In some embodiments, the oxide material coated on the carbon fibers has a thickness of 1 to 100 nm, 1 to 90 nm, 1 to 80 nm, 1 to 70 nm, 1 to 60 nm, 1 to 50 nm, 1 to 40 nm, 1 to 30 nm, 1 to 25 nm, 1 to 20 nm, 1 to 15 nm, 1 to 10 nm, 2 to 100 nm, 2 to 90 nm, 2 to 80 nm, 2 to 70 nm, 2 to 60 nm, 2 to 50 nm, 2 to 40 nm, 2 to 30 nm, 2 to 25 nm, 2 to 20 nm, 2 to 15 nm, 2 to 10 nm, 5 to 10 ... The thickness may range from 5 nm to 100 nm, 5 nm to 90 nm, 5 nm to 80 nm, 5 nm to 70 nm, 5 nm to 60 nm, 5 nm to 50 nm, 5 nm to 40 nm, 5 nm to 30 nm, 5 nm to 25 nm, 5 nm to 20 nm, 5 nm to 15 nm, 5 nm to 10 nm, 10 nm to 100 nm, 10 nm to 90 nm, 10 nm to 80 nm, 10 nm to 70 nm, 10 nm to 60 nm, 10 nm to 50 nm, 10 nm to 40 nm, 10 nm to 30 nm, 10 nm to 25 nm, 10 nm to 20 nm, 10 nm to 15 nm, or any and all ranges and sub-ranges therebetween. In some embodiments, the thickness is measured by observing a cross-section of a cut particle using a scanning electron microscope (SEM). In some embodiments, the thickness is measured by transmission electron microscope (TEM).
[0022] In one embodiment, the CAM particles have a mass percentage of 65% or greater in the composite layer.
[0023] In one embodiment, the carbon fibers coated with the oxide material have a weight percentage in the composite layer between 0.01% and 5.0% by weight.
[0024] In one embodiment, the carbon fibers coated with the oxide material have a weight percentage of between 1.0% and 3.0% by weight in the composite layer.
[0025] In one embodiment, the oxide material is an inorganic oxide material that has a wide window of voltage stability.
[0026] In one embodiment, the inorganic oxide material is B2O3, Li3B 11 O 18 , Li3BO3, Li4B2O5, Li6B4O9, LiBO2, Li2B4O7, Li3B7O 12 , LiB3O5, LiNbO3, Li4SiO4, Li3PO4, Li2SiO3, LiPO3, Li2SO4, Li2WO4, Li2MoO4, Li2ZrO3, LiAlO2, Li2TiO3, Li4Ti5O 12 or a complex oxide thereof.
[0027] In one embodiment, the inorganic oxide material is stable over a voltage range ranging from 1.9V to 5.0V.
[0028] In some embodiments, the inorganic oxide material is LiBO-doped LiCO (LCBO), where the ratio of LiCO-LiBO is: 2+x C 1-x B xIn some embodiments, 0 <x<1、0<x≦0.90、0<x≦0.80、0<x≦0.70、0<x≦0.60、0<x≦0.50、0<x≦0.45、0<x≦0.40、0<x≦0.35、0<x≦0.30、0<x≦0.25、0<x≦0.20、0<x≦0.15、0<x≦0.10、0.10≦x<1、0.10≦x≦0.90、0.10≦x≦0.80、0.10≦x≦0.70、0.10≦x≦0.60、0.10≦x≦0.50、0.10≦x≦0.45、0.10≦x≦0.40、0.10≦x≦0.35、0.10≦x≦0.30、0.10≦x≦0.25、0.10≦x≦0.20、0.15≦x<1、0.15≦x≦0.90、0.15≦x≦0.80、0.15≦x≦0.70、0.15≦x≦0.60、0.15≦x≦0.50、0.15≦x≦0.45、0.15≦x≦0.40、0.15≦x≦0.35、0.15≦x≦0.30、0.15≦x≦0.25、0.20≦x<1、0.20≦x≦0.90、0.20≦x≦0.80、0.20≦x≦0.70、0.20≦x≦0.60、0.20≦x≦0.50、0.20≦x≦0.45、0.20≦x≦0.40、0.20≦x≦0.35、0.20≦x≦0.30、0.25≦x<1、0.25≦x≦0.90、0.25≦x≦0.80、0.25≦x≦0.70、0.25≦x≦0.60、0.25≦x≦0.50、0.25≦x≦0.45、0.25≦x≦0.40、0.25≦x≦0.35、0.30≦x<1、0.30≦x≦0.90、0.30≦x≦0.80、0.30≦x≦0.70、0.30≦x≦0.60、0.30≦x≦0.50、0.30≦x≦0.45、0.30≦x≦0.40、0.35≦x<1、0.35≦x≦0.90、0.35≦x≦0.80、0.35≦x≦0.70、0.35≦x≦0.60、0.35≦x≦0.50、0.35≦x≦0.45、0.40≦x<1、0.40≦x≦0.90、0.40≦x≦0.80、0.40≦x≦0.70、0.40≦x≦0.60、0.40≦x≦0.50、0.45≦x<1、0.45≦x≦0.90、0.45≦x≦0.80、0.45≦x≦0.70、0.45≦x≦0.60、0.50≦x<1、0.50≦x≦0.90、0.50≦x≦0.80、0.50≦x≦0.70、0.50≦x≦0.60、0.70≦x<1, 0.70≦x≦0.90, 0.70≦x≦0.80, and all ranges and subranges therebetween.
[0029] In one embodiment, the solid electrolyte is a sulfur-containing inorganic electrolyte.
[0030] In one embodiment, the solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiHa, Li2S-P2S5-P2O5, Li2S-Li3PO4-P2S5, Li3PS4, Li4P2S6, Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li7P3S 11 , Li 3.25 P 0.95 S4, and Li 7-x P.S. 6-x Ha x In the formula, "Ha" is one or more halogen elements, and 0.2 <x<1.8である。
[0031] In one embodiment, the solid electrolyte has a weight percentage between 1% and 35% by weight in the composite layer. In some embodiments, the solid electrolyte may have a concentration in the range of 1% to 35% by weight, 1% to 30% by weight, 1% to 25% by weight, 1% to 20% by weight, 1% to 15% by weight, 1% to 10% by weight, 5% to 35% by weight, 5% to 30% by weight, 5% to 25% by weight, 5% to 20% by weight, 5% to 15% by weight, 10% to 35% by weight, 10% to 30% by weight, 10% to 25% by weight, 10% to 20% by weight, 15% to 35% by weight, 15% to 30% by weight, 15% to 25% by weight, 20% to 30% by weight, or any and all ranges and sub-ranges therebetween.
[0032] In one embodiment, the CAM is Li x Mn 1-y M y A2, Li x Mn1-y M y O 2-z X z , Li x MnO 4-z X z , Li x Mn 2-y M y A4, Li x Co 1-y M y A2, Li x Co 1-y M y O 2-z X z , Li x Ni 1-y M y A2, Li x Ni 1-y M y O 2-z X z , Li x Ni 1-y Co y O 2-z X z , Li x Ni 1-y-z Co y M z A a , Li x Ni 1-y-z Co y M z O 2-a X a , Li x Ni 1-y-z Mn y M z A a , Li x Ni 1-y-z Mn y M z O 2-a X a wherein 0.95≦x≦1.1, 0≦y≦0.5, 0≦z≦0.5, 0≦a≦2, M is selected from the group consisting of Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, and rare earth elements, A is selected from the group consisting of O, F, S, and P, and X is selected from the group consisting of F, S, and P.
[0033] In some embodiments, the CAM is Lix MO2, Li x Ni 1-y-z Co y M1 z O2 and Li x Ni 1-y-z Mn y M2 z O2, wherein M is at least one selected from the group consisting of Ni, Co, Mn, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn, and rare earth elements, and M1 is Mn, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, M1 is at least one selected from the group consisting of Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn, and rare earth elements, and M2 is at least one selected from the group consisting of Co, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn, and rare earth elements, and 0.95≦x≦1.1, 1-yz>0, 0 <y≦0.5、0≦z≦0.5である。
[0034] In some embodiments, the CAM is Li x MO2, Li x Ni 1-y-z Co y M1 z O2 and Li x Ni 1-y-z Mn y M2 zO2, wherein M is at least one selected from the group consisting of Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn, and rare earth elements, and M1 is Mn, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W , Rh, Pd, Cu, Zn, Cd, Ga, In, Sn, and rare earth elements, and M2 is at least one selected from the group consisting of Co, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn, and rare earth elements, and 0.95≦x≦1.1, 1-yz>0, 0 <y≦0.5、0≦z≦0.5である。
[0035] In some embodiments, the CAM is surface doped with at least one doping element selected from the group consisting of Ni, Co, Mn, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn, Si, Ge, S, P, and rare earth elements.
[0036] In some embodiments, the CAM is in the form of particles having an average diameter in the range of about 1 μm to about 15 μm, about 1 μm to about 12 μm, about 1 μm to about 10 μm, about 1 μm to about 7 μm, about 1 μm to about 6 μm, about 3 μm to about 15 μm, about 3 μm to about 12 μm, about 3 μm to about 10 μm, about 3 μm to about 7 μm, about 3 μm to about 6 μm, about 5 μm to about 15 μm, about 5 μm to about 12 μm, about 5 μm to about 10 μm, and all ranges and sub-ranges therebetween. In some embodiments, the coated CAM comprises about 50% to about 99% by weight, about 50% to about 95% by weight, about 50% to about 90% by weight, about 50% to about 85% by weight, about 50% to about 80% by weight, about 55% to about 99% by weight, about 55% to about 95% by weight, about 55% to about 90% by weight, about 55% to about 85% by weight, about 55% to about 80% by weight, about 60% to about 99% by weight, about 60% to about 95% by weight, about 60% to about 90 ... The CAM particles may have a concentration in the positive electrode layer in the range of about 85% by weight, about 60% by weight to about 80% by weight, about 65% by weight to about 99% by weight, about 65% by weight to about 95% by weight, about 65% by weight to about 90% by weight, about 65% by weight to about 85% by weight, about 65% by weight to about 80% by weight, about 70% by weight to about 99% by weight, about 70% by weight to about 95% by weight, about 70% by weight to about 90% by weight, about 70% by weight to about 85% by weight, about 70% by weight to about 80% by weight, and all ranges and subranges therebetween. In some embodiments, the CAM particles may be polycrystalline or monocrystalline. In some embodiments, the CAM particles may have a single particle size distribution or a multiple particle size distribution.
[0037] In some embodiments, the CAM contains the element Ni in a molar fraction of at least 50%, at least 55%, at least 60%, at least 65%, at least 70%, at least 75%, at least 80%, or at least 85% of all metal elements other than lithium.
[0038] In one embodiment, the particles have an average diameter of from 1 to 15 μm.
[0039] In one embodiment, the present disclosure provides an all-solid-state battery (ASSB), comprising: a) the composite layer as a positive electrode, and b) a solid electrolyte layer between the positive and negative electrodes; The present invention provides an all-solid-state battery comprising:
[0040] In one embodiment, the solid electrolyte layer is made from a second solid electrolyte, which is the same or different from the solid electrolyte in the positive electrode composite layer.
[0041] In one embodiment, the composite layer comprises at least 65% by weight particles of CAM.
[0042] In one embodiment, the ASSB has an initial discharge specific capacity of at least 180 mAh / g at a discharge rate of 0.5C.
[0043] In one embodiment, the ASSB has an initial discharge specific capacity of at least 200 mAh / g at a discharge rate of 0.1C.
[0044] In one embodiment, the ASSB has a specific capacity of at least 180 mAh / g and at least 95% capacity retention after 20 cycles at a 0.5C discharge rate.
[0045] The present disclosure will be better understood with reference to the following experimental details, although those of skill in the art will readily recognize that the specific experiments detailed are merely illustrative and are not intended to limit the present disclosure as described herein, as defined by the claims which follow.
[0046] Please note that the transitional phrase "comprising," which is synonymous with "including," "containing," or "characterized by," is inclusive or open-ended and does not exclude additional, unrecited elements or method steps. EXAMPLES
[0047] Example 1 Carbon fibers coated with oxide materials were prepared using a conventional sol-gel method. 11 O 18 For coating, stoichiometric amounts of Li precursor (e.g., lithium acetate or lithium metal) and B precursor (e.g., triisopropyl borate) were dissolved in a dry solvent (e.g., ethanol) to form a coating solution containing lithium precursor and boron precursor. A given amount of CF (VGCF-H, fiber diameter 150 nm, fiber length 10-20 μm, 13 m 2 / g BET surface area, aspect ratio of 10~500, true density 2.0g / cm 3 , apparent density VGCF (registered trademark) (standard type) 0.04g / cm 3 , single fiber resistivity 1×10 -4 The coating solution was added to a volume of 1000 Ωcm. A given amount of CF was added to determine the CF BET surface area and bulk density (Li3B 11 O 18 About 2.16g / cm 3 The mixture is stirred for 30 min, after which the solvent is removed under vacuum with sonication, resulting in a gel of CF coated with the Li and B precursors. The CF gel is then annealed at 300° C. for 1 h under flowing oxygen to give Li3B 11 O 18 The carbon fibers are coated with a CF4 layer. The specific discharge capacity and cycle life retention of various cathode layers with coated and uncoated CF4 are summarized in Table 1. The cathode layers consist of 65 wt% CAM (NCA88), 5 wt% CF (coated or uncoated), and 30 wt% LPS. The cathode layers are electrochemically evaluated in a torque cell using Li metal on copper as the anode and LPS as the SE. At 45°C, the cells were cycled from 2.8 V to 4.25 V at 0.1 C charge / discharge for cycles 1 and 2, 0.33 C charge / discharge for cycles 3 and 4, 1.0 C charge / discharge for cycle 5, and 0.5 C charge / discharge for cycles 6-25.
[0048] Carbon fibers or other electronically conductive materials are needed to electrically connect all CAM particles in the positive electrode layer to achieve high initial discharge capacity. However, the decomposition of SE in contact with CF results in significant decay. In this disclosure, a 2-50 nm thick oxide material (e.g., LBO(Li3B 11 O 18 )) addressed this. The coating thickness is stoichiometrically calculated using the BET surface area of the CF, the bulk density of the coating composition, and the mass / molar amounts of the reagents in the coating solution (assuming 100% reagent utilization). The coating thickness is confirmed by TEM analysis. A typical TEM image is shown in Figure 2.
[0049] The coated CF maintained the initial cell performance at a high level while reducing the discharge capacity fade. For example, for the half-cell containing uncoated CF, the initial discharge capacity is 205.33 mAh / g at a discharge rate of 0.1 C. For 2, 20, and 50 nm coatings of LBO on VGCF, the initial discharge capacity is 203.91 mAh / g, 206.76 mAh / g, and 219.23 mAh / g, respectively. When the thickness of LBO is 100 nm, the initial discharge capacity drops to 178.73 mAh / g. The coated CF effectively reduced the cell degradation and maintained the theoretical capacity of CAM (NCA88--LiNi 0.88 Co 0.09 Al 0.03 This may be crucial for achieving high capacity SSBs, as evidenced by the increase in initial discharge capacity at a discharge rate of 0.1C, approaching 219.8mAh / g for O2.
[0050] [Table 1] The VGCF coating is not limited to Li-containing oxides or lithium borates. Figure 4 shows 20 nm B2O3, 20 nm Li3B 11 O 18The cycling performance of uncoated VGCF with Li3BO3, 20 nm, and LiNbO3 is shown. The positive electrode layer consists of 65 wt% CAM (NCA88), 5 wt% CF (coated or uncoated), and 30 wt% LPS. The positive electrode layer is electrochemically evaluated in a torque cell using Li metal on copper as the negative electrode and LPS as the SE. The cells were cycled from 2.8 V to 4.25 V at 0.1 C charge / discharge for cycles 1 and 2, 0.33 C charge / discharge for cycles 3 and 4, 1.0 C charge / discharge for cycle 5, and 0.5 C charge / discharge for cycles 6-25. All coating compositions except Li3BO3 showed improved discharge capacity and capacity retention at the 25th cycle compared to uncoated VGCF.
[0051] [Table 2] Hereinafter, preferred embodiments of the present invention will be described item by item.
[0052] Embodiment 1 Particles of a cathode active material (CAM), a solid electrolyte, and carbon fibers coated with an oxide material, composite layer.
[0053] Embodiment 2 The composite layer according to Embodiment 1, wherein the oxide material coated on the carbon fiber has a thickness of 1 to 70 nm.
[0054] Embodiment 3 The composite layer according to Embodiment 1, wherein the oxide material coated on the carbon fiber has a thickness of 2 to 50 nm.
[0055] Embodiment 4 The composite layer according to Embodiment 1, wherein the particles of CAM have a mass percentage of 65% or more in the composite layer.
[0056] Embodiment 5 The composite layer according to Embodiment 1, wherein the carbon fibers coated with the oxide material have a mass percentage between 0.01% by mass and 5.0% by mass in the composite layer.
[0057] Embodiment 6 The composite layer according to Embodiment 1, wherein the carbon fibers coated with the oxide material have a mass percentage between 1.0% by mass and 3.0% by mass in the composite layer.
[0058] Embodiment 7 The composite layer according to Embodiment 1, wherein the oxide material is an inorganic oxide material.
[0059] Embodiment 8 The inorganic oxide material is B 2 O 3 , Li 3 B 11 O 18 , Li 4 B 2 O 5 , Li 6 B 4 O 9 , LiBO 2 , Li 2 B 4 O 7 , Li 3 B 7 O 12 , LiB 3 O 5 , LiNbO 3 , Li 4 SiO 4 , Li 3 PO 4 , Li 2 SiO 3 , LiPO 3 , Li 2 SO 4 , Li 2 WO 4 , Li 2 MoO 4 , Li 2 ZrO 3 , LiAlO 2 , Li 2 TiO 3 , Li 4 Ti 5 O 12 , and is selected from the group consisting of its composite oxides, the composite layer according to Embodiment 7.
[0060] Embodiment 9 The composite layer according to Embodiment 7, wherein the inorganic oxide material is stable over a voltage range from 1.9 V to 5.0 V.
[0061] Embodiment 10 The composite layer according to Embodiment 1, wherein the solid electrolyte is a sulfur-containing inorganic electrolyte.
[0062] Embodiment 11 The solid electrolyte is selected from the group consisting of Li 2 S-P 2 S 5 , Li 2 S-P 2 S 5 -LiHa, Li 2 S-P 2 S 5 -P 2 O 5 , Li 2 S-Li 3 PO 4 -P 2 S 5 , Li 3 PS 4 , Li 4 P 2 S 6 , Li 10 GeP 2 S 12 , Li 3.25 Ge 0.25 P 0.75 S 4 , Li 7 P 3 S 11 , Li 3.25 P 0.95 S 4 , and Li 7-x PS 6-x Ha x , wherein "Ha" is one or more halogen elements and 0.2 < x < 1.8, the composite layer according to Embodiment 1.
[0063] Embodiment 12 The composite layer according to Embodiment 1, wherein the solid electrolyte has a mass percentage between 1% by mass and 35% by mass in the composite layer.
[0064] Embodiment 13 The CAM is Li x MO 2 , Li x Ni 1-y-z Co y M1 z O 2 and Li xNi 1-y-z Mn y M2 z O 2 At least one selected from the group consisting of, wherein M is at least one selected from the group consisting of Ni, Co, Mn, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn, and rare earth elements; M1 is at least one selected from the group consisting of Mn, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn, and rare earth elements; M2 is at least one selected from the group consisting of Co, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn, and rare earth elements; 0.95 ≦ x ≦ 1.1, 1 - y - z > 0, 0 < y ≦ 0.5, 0 ≦ z ≦ 0.5, the composite layer according to Embodiment 1.
[0065] Embodiment 14 The composite layer according to Embodiment 1, wherein the particles have an average diameter of 1 to 15 μm.
[0066] Embodiment 15 An all-solid-state battery (ASSB), a) The composite layer according to Embodiment 1 as a positive electrode, b) A negative electrode layer, and c) A solid electrolyte layer between the positive electrode and the negative electrode, The ASSB comprising.
[0067] Embodiment 16 The ASSB according to Embodiment 15, wherein the solid electrolyte layer is the same as or different from the solid electrolyte in the positive electrode composite layer.
[0068] Embodiment 17 The ASSB according to Embodiment 15, wherein the composite layer contains at least 65% by mass of CAM particles.
[0069] Embodiment 18 The ASSB according to Embodiment 17, wherein the ASSB has an initial discharge specific capacity of at least 180 mAh / g at a discharge rate of 0.5C.
[0070] Embodiment 19 The ASSB according to Embodiment 17, wherein the ASSB has an initial discharge specific capacity of at least 200 mAh / g at a discharge rate of 0.1C.
[0071] Embodiment 20 18. The ASSB of embodiment 17, wherein the ASSB is charged to 4.25 V and discharged to 2.8 V at 45° C. at 0.1 C for cycles 1 and 2, at 0.33 C for cycles 3 and 4, at 1.0 C for cycle 5, and at 0.5 C for cycles 6 to 20 for a total of 20 cycles, and the ASSB exhibits a specific capacity of at least 180 mAh / g at the 20th cycle and a cycle life retention of at least 95%, wherein the cycle life retention is the ratio of the discharge specific capacity at the 20th cycle to the initial discharge specific capacity at 45° C. and 0.5 C.
Claims
1. Particles of positive electrode active material (CAM), A solid electrolyte, and Carbon fibers coated with an oxide material; A composite layer comprising:
2. The composite layer of claim 1 , wherein the oxide material coated on the carbon fibers has a thickness of 1 to 70 nm.
3. The composite layer of claim 1 , wherein the oxide material coated on the carbon fibers has a thickness of 2 to 50 nm.
4. The composite layer of claim 1 , wherein said particles of CAM have a mass percentage of 65% or greater in said composite layer.
5. The composite layer of claim 1 , wherein the carbon fibers coated with the oxide material have a weight percentage in the composite layer between 0.01% and 5.0% by weight.
6. The composite layer of claim 1 , wherein the carbon fibers coated with the oxide material have a weight percentage in the composite layer between 1.0% and 3.0% by weight.
7. The composite layer of claim 1 , wherein the oxide material is an inorganic oxide material.
8. The inorganic oxide material is B 2 O 3 , Li 3 B 11 O 18 , Li 4 B 2 O 5 , Li 6 B 4 O 9 , LiBO 2 , Li 2 B 4 O 7 , Li 3 B 7 O 12 , LiB 3 O 5 , LiNbO 3 , Li 4 SiO 4 , Li 3 P.O. 4 , Li 2 SiO 3 , LiPO 3 , Li 2 SO 4 , Li 2 WO 4 , Li 2 MoO 4 , Li 2 ZrO 3 , LiAlO 2 , Li 2 TiO 3 , Li 4 Ti 5 O 12 8. The composite layer according to claim 7, wherein the metal oxide is selected from the group consisting of arsenic, arsenic oxide ... and complex oxides thereof.
9. The composite layer of claim 7 , wherein the inorganic oxide material is stable over a voltage range ranging from 1.9V to 5.0V.
10. The composite layer of claim 1 , wherein the solid electrolyte is a sulfur-containing inorganic electrolyte.
11. The solid electrolyte is Li 2 S-P 2 S 5 , Li 2 S-P 2 S 5 - LiHa, Li 2 S-P 2 S 5 -P 2 O 5 , Li 2 S-Li 3 P.O. 4 -P 2 S 5 , Li 3 P.S. 4 , Li 4 P 2 S 6 , Li 10 GeP 2 S 12 , Li 3.25 Ge 0.25 P 0.75 S 4 , Li 7 P 3 S 11 , Li 3.25 P 0.95 S 4 , and Li 7-x P.S. 6-x Ha x 2. The composite layer of claim 1, wherein "Ha" is one or more halogen elements and 0.2<x<1.
8.
12. 10. The composite layer of claim 1, wherein the solid electrolyte has a weight percentage of between 1% and 35% by weight in the composite layer.
13. The CAM is Li x M.O. 2 , Li x Ni 1-y-z Co y M1 z O 2 and Li x Ni 1-y-z Mn y M2 z O 2 In the formula, M is at least one selected from the group consisting of Ni, Co, Mn, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn, and rare earth elements, and M1 is Mn, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn , Cd, Ga, In, Sn, and at least one selected from the group consisting of rare earth elements, and M2 is at least one selected from the group consisting of Co, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn, and rare earth elements, and 0.95≦x≦1.1, 1-y-z>0, 0<y≦0.5, 0≦z≦0.
5.
14. The composite layer of claim 1, wherein the particles have an average diameter of 1 to 15 μm.
15. An all-solid-state battery (ASSB), a) the composite layer according to claim 1 as a positive electrode; b) a negative electrode layer, and c) a solid electrolyte layer between the positive electrode and the negative electrode; ASSB equipped with.
16. 16. The ASSB of claim 15, wherein the solid electrolyte layer is the same as or different from the solid electrolyte in the positive electrode composite layer.
17. The ASSB of claim 15 , wherein the composite layer comprises at least 65% by weight of particles of CAM.
18. 20. The ASSB of claim 17, wherein the ASSB has an initial discharge specific capacity of at least 180 mAh / g at a discharge rate of 0.5C.
19. 20. The ASSB of claim 17, wherein the ASSB has an initial discharge specific capacity of at least 200 mAh / g at a discharge rate of 0.1 C.
20. 18. The ASSB of claim 17, wherein the ASSB is charged to 4.25 V and discharged at 45° C. at 0.1 C for cycles 1 and 2, at 0.33 C for cycles 3 and 4, at 1.0 C for cycle 5, and at 0.5 C for cycles 6 through 20 to 2.8 V for a total of 20 cycles, and wherein the ASSB exhibits a specific capacity of at least 180 mAh / g at the 20th cycle and a cycle life retention of at least 95%, wherein the cycle life retention is the ratio of the discharge specific capacity at the 20th cycle to the initial discharge specific capacity at 45° C. and 0.5 C.
Citation Information
Patent Citations
Composite material, method for producing the same and all-solid-state lithium ion secondary battery
JP2021172545A
Positive electrode material, secondary battery, and methods respectively for producing positive electrode material and secondary battery
US20150228966A1
Electrical insulating vapor grown carbon fiber and method for producing the same, and use thereof
US7150911B2
Battery electrode structure
US9219271B2